2020
DOI: 10.1103/physrevphyseducres.16.020117
|View full text |Cite
|
Sign up to set email alerts
|

Physics teacher isolation, contextual characteristics, and student performance

Abstract: Physics, as a foundational science, has particular importance in predicting the postsecondary success of students who major in science, technology, engineering, and mathematics. This quasiexperimental, observational study examined teacher-level and school-level predictors of student performance in physics, with a focus on isolated teachers. A New York State case study is useful since the teacher certification policy is largely determined at the state level in the U.S. The overall sample included New York State… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…High school academic course selection is an important consideration in engineering admissions, since post-secondary success in engineering study has often been linked to precollege course preparation in advanced mathematics and science (May and Chubin 2003;Tyson 2011). However, access to such courses has been inequitable in terms of ethnicity and socioeconomic status (Kelly and Sheppard 2009, 2010, 2019Krakehl et al 2020;National Center for Science and Engineering Statistics 2018;Padwa et al 2019;Sheppard et al 2020). Teachers may be influenced by latent biases concerning which students are best suited for engineering (Nathan et al 2010).…”
Section: Fostering Stem Preparation and Aspirationsmentioning
confidence: 99%
“…High school academic course selection is an important consideration in engineering admissions, since post-secondary success in engineering study has often been linked to precollege course preparation in advanced mathematics and science (May and Chubin 2003;Tyson 2011). However, access to such courses has been inequitable in terms of ethnicity and socioeconomic status (Kelly and Sheppard 2009, 2010, 2019Krakehl et al 2020;National Center for Science and Engineering Statistics 2018;Padwa et al 2019;Sheppard et al 2020). Teachers may be influenced by latent biases concerning which students are best suited for engineering (Nathan et al 2010).…”
Section: Fostering Stem Preparation and Aspirationsmentioning
confidence: 99%
“…From the teaching experience of the teachers, Krakehl et al (2020), added that physics teachers' years of teaching experience have a significant effect on increasing students' achievement, compared to teachers with less experience, which will lead to low students' achievement. According to Alamsyah et al (2020), teachers' teaching experience significantly influences the students learning achievement because it significantly influences the teachers professionalism.…”
Section: ) the Utilization Of Science Laboratory Facilities By The Te...mentioning
confidence: 99%
“…10 In terms of disciplinary focus, studies have confirmed that science and mathematics have experienced chronic turnover, 23−25 particularly in lower socioeconomic schools where mathematics and science turnover rates are nearly 70% greater than higher socioeconomic schools. 7 Studies have suggested that teaching in isolation may lead to higher levels of turnover, 2,40,41 often due to increased levels of occupational stress and decreased self-efficacy stemming from limited access to collaboration and feedback from other teachers within the same content area. 14,42−46 In a recent study, isolated teachers had a higher likelihood of being in their first five years of teaching, working in a high-needs school district, and teaching out-of-field.…”
Section: Contextual Factors Influencing Teacher Turnovermentioning
confidence: 99%
“…Studies have suggested that teaching in isolation may lead to higher levels of turnover, ,, often due to increased levels of occupational stress and decreased self-efficacy stemming from limited access to collaboration and feedback from other teachers within the same content area. , In a recent study, isolated teachers had a higher likelihood of being in their first five years of teaching, working in a high-needs school district, and teaching out-of-field. Approximately two-thirds of these isolated chemistry teachers taught in lower performing, lower socioeconomic schools .…”
Section: Review Of the Literaturementioning
confidence: 99%